Effect of scale and saturation on ffective properties of porous rocks for seismic monitoring of CO2 sequestration - Caspari, Eva (Curtin University, 2013)
Prediction of the time-lapse seismic signal caused by CO2 saturation effects requires knowledge about the geospatial distribution of fluids and the elastic properties of the storage formation. To obtain meaningful predictions representative effective properties of the reservoir are crucial. The thesis focus is the effect of scale and CO2 saturation on effective properties of porous rocks in a time-lapse seismic study with emphasis on elastic property –porosity relations, velocity-saturation relations and effective hydraulic conductivity.